Integrated Dry-Fermented Catfish Production to Promote Sustainable Livelihoods and Community-Based Economic Development: A Case Study of the Community Enterprise Group in Koh Tao Subdistrict, Pa Phayom District, Phatthalung Province, Thailand - Thanonkaew, Amonrat; Klompong, Vilailak; Mayachiew, Pornpimon; Luanunkarb, Thanidchaya; Hoktha, Pimchana; Intarat, Naruemon; Phatcharasit, Kritsada; Panomjan, Nantiya; Kiriratnikom, Suphada (Area Based Development Research Journal, 2025)
Background: The Community Enterprise Group for Agricultural Product Processing in Village 13, Koh Tao Subdistrict, Pa Phayom District, Phatthalung Province, in Southern Thailand has pioneered an integrated approach to catfish farming and dry-fermented catfish (pla-duk-ra) production. The group engages in both aquaculture—raising hybrid and African catfish—and in processing, distributing fresh catfish and fermented products. However, its members historically faced significant obstacles. Catfish farming incurred high production costs, fingerling shortages occurred during the rainy season, and many earthen ponds were in poor condition. Processing methods lacked compliance with basic Good Manufacturing Practices (GMP), producing inconsistent quality. Drying facilities were insufficient, packaging failed to preserve freshness, and members had little knowledge of developing ready-to-eat products or adding value to by-products. To address these challenges, an integrated program was implemented with 40 vulnerable households and community members. The intervention was structured into five stages: (1) improving aquaculture methods, (2) upgrading processing to meet GMP standards, (3) conducting product quality analysis, (4) diversifying product lines into ready-to-eat foods and by-products, and (5) improving packaging and labeling to meet legal and commercial requirements. Processing and Quality Enhancement: Hybrid catfish and African catfish were raised in canvas ponds as an alternative to deteriorating earthen ponds. Results indicated that African catfish grew faster and required lower feed costs than hybrid catfish, significantly reducing production risks. This innovation not only ensured a consistent supply of raw material but also stabilized farm-level incomes. Processing systems were redesigned to meet basic GMP standards. New facilities were constructed, formulas were refined, and workflows were simplified, reducing processing time while increasing monthly production capacity from just 50 kilograms to 200–300 kilograms. Comparative quality analysis revealed that African catfish yielded fermented products with higher protein, lower fat, and sensory qualities equivalent to those made from hybrid catfish, thereby validating African catfish as a cost-effective and high-quality alternative raw material. Product Diversification, Packaging, and Branding: The group expanded beyond traditional pla-duk-ra by developing innovative ready-to-eat products and by-products. New items included sweet fish sauce, ready-to-eat fried pla-duk-ra, pla-duk-ra chili paste, and rice seasoning powder. By utilizing fish parts such as heads (22%), intestines (2.1%), and fat (4.9%), waste was minimized, consistent with circular economy principles. Defective or unsellable fermented fish (3%) were repurposed into chili paste and seasoning, thereby transforming potential losses into marketable goods. A major breakthrough came from the development of attractive, durable, and legally compliant packaging. Improved designs enhanced shelf life, protected product quality, and increased consumer confidence. The enterprise also introduced proper labeling with clear production details, supporting compliance with food safety standards and strengthening market competitiveness. Economic and Environmental Impacts: Before the intervention, the enterprise offered only two products: hybrid catfish and dry-fermented catfish, generating 21,600 Baht per month (≈USD 620) with a net profit of 5,100 Baht (≈USD 146). After expansion, the product portfolio grew to seven items: hybrid catfish, African catfish, pla-duk-ra, sweet fish sauce, ready-to-eat fried pla-duk-ra, pla-duk-ra chili paste, and rice seasoning. Income from hybrid catfish rose from 6,600 Baht (≈USD 189) to 16,500 Baht (≈USD 472), an increase of 150%. Income from pla-duk-ra surged from 15,000 Baht (≈USD 429) to 60,000 Baht (≈USD 1,714), a 300% increase. African catfish added 10,000 Baht per month (≈USD 286), while the new products collectively contributed 4,500 Baht (≈USD 129) monthly. Overall, total revenue increased from 21,600 Baht (≈USD 620) to 91,000 Baht (≈USD 2,600) per month, a remarkable 321.3% growth, while net profit rose from 5,100 Baht (≈USD 146) to 22,750 Baht (≈USD 650), a 346.1% increase. Environmental benefits were equally notable. Canvas pond farming improved water efficiency and reduced land use compared to earthen ponds, while better water management minimized risks of pollution to natural waterways. Solar-powered dryers replaced fossil fuel use, cutting greenhouse gas emissions. Circular economy practices—turning by-products into secondary goods—minimized waste while creating additional revenue streams. Packaging innovations further reduced food loss during storage and distribution. Sustainable Development of Human and Social Capital: The initiative also built human and social capital within the community. Training in aquaculture, processing, and quality control enhanced vocational skills transferable to future generations. Vulnerable groups gained employment, improving household security. Knowledge-sharing among members fostered cooperation, while partnerships with universities and government agencies expanded technical support. Moreover, the initiative preserved local wisdom: pla-duk-ra is a traditional food of Phatthalung Province, and its modernization reflects a successful integration of indigenous practices with modern technology. The integrated dry-fermented catfish model reflects the principles of sufficiency economy by balancing economic, social, and environmental dimensions. Economically, diversified products reduce dependency on a single income stream while ensuring stable growth. Socially, the initiative strengthened community bonds, preserved cultural heritage, and empowered vulnerable groups. Environmentally, the adoption of renewable energy and efficient resource use reinforced sustainable practices. For long-term resilience, the group must continue to build strategic management capacity, foster innovation, and prepare new leadership to sustain operations across generations. Conclusion: The case of this enterprise group demonstrates how integrated aquaculture and value-added processing can transform rural livelihoods. By combining improved production methods, product diversification, branding, and sustainability principles, the initiative not only enhanced household incomes but also strengthened social cohesion and environmental stewardship. The model illustrates a viable pathway for rural communities in Thailand and beyond to achieve inclusive and sustainable economic development.